Laparoscopic vs. open distal gastrectomy for locally advanced gastric cancer: A systematic review and meta-analysis of randomized controlled trials - Yan, Yong; Ou, Caiwen; Cao, Shunwang; Hua, Yinggang; Sha, Yanhua (Frontiers in Surgery, 2023)
Objective: The aim of this systematic review and meta-analysis was to compare the short- and long-term outcomes of LDG versus ODG for patients with advanced gastric cancer (AGC) exclusively undergone distal gastrectomy and D2 lymphadenectomy in randomized controlled trials (RCTs). Background: Data in published meta-analyses included different gastrectomy types and mixed tumor stages prevented an accurate comparison between LDG and ODG. Recently, several RCTs compared LDG versus ODG included AGC patients specifically for distal gastrectomy with D2 lymphadenectomy have reported and updated with the long-term outcomes. Methods: PubMed, Embase, and Cochrane were searched to identify RCTs compared LDG versus ODG for advanced distal gastric cancer. The short-term surgical outcomes, mortality, morbidity and long-term survival were compared. The Cochrane tool and GRADE approach were used for evaluating evidence quality (Prospero registration ID: CRD42022301155). Results: Five RCTs concerning total 2746 patients were included. Meta-analyses showed no significant differences in intraoperative complications, overall morbidity, severe postoperative complications, R0 resection, D2 lymphadenectomy, recurrence, 3-year disease-free survival, intraoperative blood transfusion, time to first liquid diet, time to first ambulation, distal margin, reoperation, mortality or readmission between LDG and ODG. Operative times were significantly longer for LDG (WMD 49.2 minutes, P < 0.05), whereas harvested lymph nodes, intraoperative blood loss, postoperative hospital stay, time to first flatus and proximal margin were lower for LDG (WMD -1.3, P < 0.05; WMD -33.6 ml, P < 0.05; WMD -0.7 day, P < 0.05; WMD -0.2 day, P < 0.05; WMD -0.4 mm, P < 0.05). The intra-abdominal fluid collection and bleeding were noted less after LDG. Certainty of evidence was moderate to very low. Conclusions: Data from five RCTs suggests that LDG with D2 lymphadenectomy for AGC has similar short-term surgical outcomes and long-term survival compared to ODG when performed by experienced surgeons in high volume hospitals. Further RCTs should address the potential advantages of LDG for AGC.